Adsorption of cadmium using regular MgAIC03 layered double hydroxide (LDHsf) / Norzuyati Mohd Aris - Mohd Aris, Norzuyati (Faculty of Applied Sciences, 2009)
Heavy metal pollution had become one of the environmental problems which cause several diseases either to human, animal or plant. In this study, MgAlCCb layered double hydroxide was investigated as an alternative low-cost adsorbent for the removal of cadmium (Cd) from aqueous solution. MgAICO} was synthesized by using coprecipitation method at room temperature. X-ray diffractogram showed the presence of sharp and intense line with d-spacing 7.87215 A and the interlayer spacing of the sample was found to be 3.92687 A showed general features of hydrotalcite. The contact time required to obtain the maximum adsorption of cadmium was 180 min at the concentration of 150 ppm. The adsorption increases gradually as the pH and adsorbent dosage increase. However, the adsorption is inversely proportional with the increase of temperature which showed that this reaction is an exothermic reaction. The data on cadmium fit well on Langmuir and Freundlich. This study indicates that MgAlCCVLDHs has the ability to remove cadmium from aqueous solution.